Activation of MET promotes resistance to sorafenib in hepatocellular carcinoma cells via the AKT/ERK1/2-EGR1 pathway - Qing-Feng Xiang; Mei-Xiao Zhan; Yong Li; Hui Liang; Cong Hu; Yao-Ming Huang; Jing Xiao; Xu He; Yong-Jie Xin; Min-Shan Chen; Li-Gong Lu (Artificial Cells, Nanomedicine, and Biotechnology, 2019)
Sorafenib is an oral multikinase inhibitor that has become an established therapeutic approach in advanced hepatocellular carcinoma (HCC). However, the benefit of sorafenib in clinical therapy is often affected by drug resistance. Therefore, it is important to explore the mechanisms underlying sorafenib resistance and to develop individualized therapeutic strategies for coping with this problem. In this study, we found that addition of HGF to sorafenib-treated HCC cells activated MET and re-stimulated the downstream AKT and ERK1/2 pathways. Thereby, restored sorafenib-treated HCC cells proliferation, migration and invasion ability, and rescued cells from apoptosis. In addition, we found that HGF treatment of HCC cells induced early growth response protein (EGR1) expression, which is involved in sorafenib resistance. Importantly, the HGF rescued effect in sorafenib-treated HCC cells could be abrogated by inhibiting MET activation with PHA-665752 or by downregulating EGR1 expression with small interfering RNA (siRNA). Therefore, inhibition of the HGF/MET pathway may improve response to sorafenib in HCC, and combination therapy should be further investigated.